Binding mechanism of full-length Aβ40 peptide to a mixed lipid bilayer - Wang, Ke; Cai, Wensheng (Frontiers in Chemistry, 2024)
The destructive effect of Aβ peptides to membrane is an important source of its cytotoxicity in the pathogenesis of Alzheimer’s Disease. We have investigated the binding between Aβ42 peptide and bilayer in our former work. However, as another abundant form of Aβ peptides in physiological environment, the binding mechanism between Aβ40 peptide and the lipid bilayer still remains ambiguous. Hence, we performed all-atom simulations on the Aβ40 peptides with the lipid bilayer herein using replica exchange with solute tempering 2 method. We have obtained four major binding models with the hydrophobic C-terminus as the most preferable binding region. Hydrophobic residues and positively charged residues are principal residues involved in the peptide-bilayer interactions. Aβ40 peptides in our simulation mainly adopt β-rich conformation in both bound and unbound states. Besides, we have determined peptide-water interactions, and found that bound peptides prefer forming hydrogen bonds with water molecules than unbound peptides. Our findings herein may provide new insights for the in-depth understanding of the membrane destructive mechanism of Aβ peptides.